Hexavalent Chromium-induced Changes in Biochemical Parameters of Wistar Albino Rats - Ounassa Adjroud (International Conference on Biological and Chemical Processes (ICBCP), 25-26 April, 2016)
Potassium dichromate (K2Cr2O7) is one of the most toxic elements to which man can be exposed at work or in the environment. The purpose of the current work is to compare the effect of K2Cr2O7 using variations in the dose, route of administration and duration of exposure in male and female Wistar albino rats with a special focus on biochemical parameters. K2Cr2O7 was subcutaneously administered alone (10, 50 and 100 mg/kg body weight) to female Wistar albino rats. Male rats received in their drinking water K2Cr2O7 30 mg/L/day) for 20 consecutive days. The Biochemical parameters were evaluated on days 3, 6 and 21 after subcutaneous (sc.) treatment in female rats and on days 10 and 20 after oral administration in male rats. The subcutaneous (s.c.) administration of 25 mg/kg of K2Cr2O7 to Wistar albino rats induced a slight change in plasma glucose levels during the experiment period. On the contrary, a significant decrease in plasma glucose levels was observed with 50 mg/kg mainly on days 3 (-26%) and 21 (-48%) after treatment compared to controls females rats. On the other hand, the higher dose provoked a significant increase in plasma glucose concentrations on days 6 (+31%) and 21 (+60%). similarly, the lower dose of chromium had no effect on the plasma urea levels. Conversely, a significant increase (122%) in this parameter was obtained during the first three days after treatment. In addition, a significant decrease in plasma glucose levels was observed with 50 mg/kg mainly on days 3 (-26%) and 21 (-48%) after treatment. On the other hand, the higher dose provoked a significant increase in plasma glucose concentrations on days 6 (+31%) and 21 (+60%). similarly, the lower dose of chromium had no effect on the plasma urea levels. Conversely, a significant increase in this parameter (122%) was obtained during the first three days after treatment. In addition, administration of 100 mg/kg of K2Cr2O7 by s.c markedly augmented the levels of plasma urea on days 3 (62%) and 6 (121%). Administration of 30 mg/L/day of K2Cr2O7 in the drinking water induced a significant augmentation in both of plasma glucose (27%) and urea (126%) during the first ten days of treatment. These results suggested that K2Cr2O7 administered subcutaneously or in the drinking water may induce harmful effects on biochemical parameters. Keywords : glucose, potassium dichromate, Wistar albino rat, urea.